Concentration of Heavy Metals (Pb and Cu) in Alepes vari and Johnius belangerii from Musi River Estuary, Banyuasin District, South Sumatra - Fitri Agustriani; Anna Ida Sunaryo Purwiyanto; Wike Ayu Eka Putri; Fauziyah Fauziyah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Agustriani F, Purwiyanto AIS, Putri WAE, Fauziyah. 2019. Concentration of heavy metals (Pb and Cu) in alepes vari and johnius belangerii from musi river estuary, Banyuasin district, South Sumatra. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):213-219. The Musi river estuary plays an important role as one of the fishing grounds. The high activity in the musi estuary has an impact on the ecosystems in this region, including the negative impact in the form of ecosystem changes caused by heavy metals. The aim of this study was to determine the concentrations of heavy metals (Pb and Cu) in Alepesvariand Johniusbelangerii in the Musi river estuary. Fish were obtained from fishermen who used the Gillnet Millennium (Ply) gear in July 2018 and were analyzed using the Atomic Absorption Spectrophotometer (AAS). The results showed that the concentration of Pb in J. belangerii was greater than A. vari, but the concentration of Cu in A. vari was greater than in J. belangerii. Concentration of Pb has exceeded the limit for safe consumption based on National Agency of Drug and Food Control.